Meningkatkan Karakter Kerjasama Melalui Model Pembelajaran Berbasis Proyek pada Materi Manajemen Produksi Seni Pertunjukan. - Ramadani, Zulri; Kusumawardani, Dwi; Mutiara Sari, Kartika (Jurnal Pendidikan Tari, 2022)
This study aims to analyze the learning process and outcomes of the application of project-based learning in performing arts production management materials to improve students' cooperative character. The problem in this research is student attitudes and learning that have not led to activities that require cooperation. This study uses the classroom action research method (CAR) from Kurt Lewin. Two cycles were used in this study. In each cycle there are four stages, namely planning (Planning), action (Action), observation (Observing), and reflection (Reflecting). The research took place from January to June 2022 at SMA Negeri 1 Silangkitang, South Labuhanbatu, North Sumatra, through courageous learning because it was still during the Covid-19 pandemic. Data was collected through data collection in the form of questionnaires, observations, interviews, and documentation. The results showed that applying project-based learning models in performing arts production management materials could increase the attitude of cooperation based on the results in the pre-cycle by 57.5%, the first cycle increased by 86.04%, and the second cycle by 95.10%. The conclusion of this study is the use of project-based learning models in performing arts production management materials to improve the character of successful student collaboration and increase each individual student.